Investigation of Antibiotic Resistance Profiles and Carbapenemase Resistance Genes in Acinetobacter Baumannii Strains Isolated From Clinical Samples - Karabay, Osman; Ekşi, Fahriye; Yıldırım, Mehmet Sait; Gazel, Deniz (European Journal of Therapeutics, 2022)
Objective: Acinetobacter baumannii is an important pathogen that can develop multiple drug resistance. Here, we aimed to investigate the antibiotic resistance profiles of A. baumannii strains isolated from the various clinics of our hospital and determine the class D beta-lactamase resistance genes causing carbapenem resistance. Methods: Between June-2016 and June-2017, 157 A. baumannii strains isolated from clinical specimens of our hospital were identified with automatic bacterial identification system and antibiograms were determined by the same system. Among the carbapenem resistant strains, blaOXA-51, blaOXA-58, blaOXA-23 and blaOXA-24 genes were also investigated by PCR method. Results: When we analyze the resistance profiles of the strains, we observed that the lowest resistance rate was against colistin with 5 (3.2%) strains. OXA-51 and OXA-23 genes were found positive in all isolates, while OXA-24 was found positive in 16 (32%) strains; OXA-58 was not detected in any of the strains. Conclusion: The most effective antibiotics for carbapenem resistant A. baumannii isolates were colistin, tigecycline and amikacin. Prevelance of OXA-24 enzyme gene was found higher than other similar studies. Monitoring antibiogram profiles and conducting molecular epidemiological studies may help us detect resistant bacteria at the source and reduce the development of resistance.